Summerfield scaling model and electrical conductivity study for understanding transport mechanisms of a Cr3+ substituted ZnAl2O4 ceramic. Issue 5 (23rd January 2023) - Elhamdi, I.; Mselmi, F.; Souissi, H.; Kammoun, S.; Dhahri, E.; Sanguino, P.; Costa, B. F. O.
Abstract : We have adopted two methods, sol–gel and solid-state synthesis methods to show the effect of grain size and the effect of temperature in the conductivity study. Abstract : Solid-state and sol–gel procedures were used to prepare ZnAl1.95 Cr0.05 O4 nanocrystal spinels. From the results obtained by X-ray diffraction (XRD) and transmission electron microscopy (TEM), it can be concluded that the samples prepared by sol–gel synthesis are better crystallized than the ones resulting from the solid-state method. Studies by spectroscopy of impedance were done in function of frequency (40–10 7 Hz) and temperature (540–680 K) in the sample prepared by sol–gel synthesis. The electrical conductivity spectra obey Jonscher's law and two models were observed studying the variation of the exponent 's' as a function of temperature, Correlated Barrier Hopping (CBH) and Non-overlapping Small Polaron Tunnelling (NSPT). The predominant conduction mechanism is bipolaron hopping. The scaling behavior of conductivity spectra was checked by Summerfield scaling laws. The time–temperature superposition principle (TTSP) points to a common transport mechanism working for the low and middle frequency ranges. The scaling mechanism fails in the high-frequency ranges suggesting that conduction dynamics, and the usual hopping distance of mobile species, have changed. The values obtained for the activation energy from the hopping frequency, conductivity σ dc, bulk resistance R gb, and relaxation ( f max ), in the temperature range of 540–680 K, are very close. A higher and negative temperature coefficient of resistivity (TCR coefficient) equal to −2.7% K −1 is found at 560 K. This result shows that our compound is suitable for uncooled infrared bolometric applications and infrared detectors.